Optimalisasi Pemberdayaan Potensi Lokal Melalui Inovasi Tepat Guna Menuju Masyarakat Desa Sukaharja yang Mandiri - Septiani Agustien, Gina; Khindiq, Ihsanul; Anastasya, Dina (Journal of Empowerment Community, 2026)
The Community Empowerment and Learning Community Service Program (KKN-PPM) of the University of Struggle Tasikmalaya was held in Sukaharja Village, Sariwangi District, Tasikmalaya Regency, aiming to increase community independence through optimizing local potential. The implementation method used a participatory approach in six focus areas: education, health, economy, environment, disaster mitigation, and institutions. As a result, there was an increase in community knowledge and skills in agricultural product management, digital marketing, and environmental management. The formation of assisted groups such as waste banks and digital Micro, Small, and Medium Enterprises (KKN) is an indicator of the program's success and sustainability. It was concluded that this collaborative strategy based on local potential is effective as a catalyst for change towards an independent and sustainable village community.